NILAI-NILAI KEARIFAN LOKAL DALAM PANDANGAN HIDUP MASYARAKAT ADAT KAMPUNG KUTA - Sukmayadi, Trisna (Universitas Muhammadiyah Ponorogo, 2018)
This study aims to explore that the values of local wisdom based on indigenous people. In addition, to develops the character of civic disposition in Kuta Village and its implementation in the level of schooling. The research methodology uses a qualitative approach with case study method. The data was collected by the study of literature, interview, observation and documentation. The results showed that two part of main data. First of all, the values of the character within the indigenous village of Kuta is reflected in the art, the adage (proverb Sunda), and outlook of life, which consists of a soft character, orderly, efficiency, and discipline. Moreover, mutual love, mutual maintain, teach each other, sincere, obedient or submissive, visionary (thinking ahead), responsible, dedicated, loyalty, sympathy, empathy, compassion, tolerance, sacrifice, devotion, faith and piety, simple, humble, appreciative health, thoughtful, and constructive thinking. Secondly, the implementation of the values of local wisdom in the level of schooling can be through the subject of Civic education, integration in every subject, habituation (habit) of the school and in extra-curricular integration.